Experiments in financial democracy corporate governance and financial development in Brazil - Musacchio Farias, Aldo. (New York Cambridge University Press, 2009)
"This book is a detailed historical description of the evolution of corporate governance and stock markets in Brazil in the late nineteenth and twentieth centuries. The analysis details the practices of corporate governance, in particular the rights that shareholders have to restrict the actions of managers, and how that shaped different approaches to corporate finance over time. The book argues that companies are not necessarily constrained by the institutional framework in which they operate. In the case of Brazil, even if the protections for investors included in national laws were relatively weak before 1940, corporate charters contained a series of provisions that protected minority shareholders against the abuses of large shareholders, managers, or other corporate insiders. These provisions ranged from limits on the number of votes a single shareholder could have to restrictions on the number of family members who could act as directors simultaneously. The investigation uses the Brazilian case to challenge some of the key findings of a recent literature that argues that legal systems (e.g., common vs. civil law) shape the extent of development of stock and bond markets in different nations. The book argues that legal systems alone cannot determine the course of stock and bond markets over time, because corporate governance practices and the size of these markets vary significantly over time, while the basic principles of legal systems are stable"
Includes bibliographical references and index.
Keywords: Stockholders--Brazil--History.